Legal Choice and Inheritance Negotiation in a Plural Legal Order: Typologies and Determinants in Padang Sidempuan, Indonesia - Mahmud Dongoran; Syamruddin Nasution; Peri Pirmansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study addresses the problem of legal choice in inheritance distribution within Indonesia’s plural legal system, where Islamic inheritance law (farā’iḍ) and customary law coexist but often operate in tension. Focusing on Padang Sidempuan, a predominantly Muslim society characterized by a strong Batak Angkola patrilineal structure, this research aims to analyze how inheritance decisions are determined and negotiated in practice. Using a qualitative socio-legal approach, the study examines six inheritance cases (2023–2024) through in-depth interviews with 18 informants, analysis of Religious Court decisions, and relevant documentary evidence. The data were analyzed thematically to identify patterns of legal choice and dispute resolution. The findings reveal three distinct typologies of inheritance settlement: first, full application of Islamic inheritance law, second, dominance of customary law, and third, a negotiated hybrid model combining elements of both systems. The study further demonstrates that legal choice is shaped by the interaction of six key factors: religious literacy, patrilineal kinship structure, social authority, institutional access, economic value of assets, and gender awareness. Rather than reflecting rigid normative conflict, inheritance practices operate through dynamic processes of social negotiation that produce context-specific outcomes. Theoretically, this study contributes to the discourse on legal pluralism by conceptualizing inheritance decisions as negotiated and adaptive processes. Empirically, it provides a structured model for understanding legal choice in inheritance practices within patrilineal Muslim societies.